HISTOPATHOLOGY OF Mystus nemurus LIVER THAT WERE FED WITH FEED ADDED WITH Psidium guajava AND Andrographis paniculata NESS - Jumaida '; Morina Riauwaty S; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on June to August 2014 in the Laboratory of Parasitesand Diseases of Fisheris and Marine Science of Faculty Riau University Pekanbaru. Thepurpose of this research was to determine the structure of (Mystus nemurus) liver that werefed with feed added with Psidium guajava and Andrographis paniculata Ness. The methodused is an experimental using 3 treatments with 3 replicated. The treatment used in thisresearch was Kn (Fishes were not receive any treantent), Kp (Fishes were not receive anytreatment but were infected with A. hydrophila), P1 ( Fishes were fed with feed added with10 g of Psidium guajava and 10 g of Andrographis paniculata Ness and were infected withA. hydrophila (0.1 ml of 108 of A. hydrophila culture), P2 (Fishes were fed with feed addedwith 20 g of Psidium guajava and 20 g of Andrographis paniculata Ness and were infectedwith A. hydrophila (0.1 ml of 108 of A. hydrophila culture), P3 (Fishes were fed with feedadded with 30 g of Psidium guajava and 30 g of Andrographis paniculata Ness and wereinfected with A. hydrophila (0.1 ml of 108 of A. hydrophila culture). Fish organ (liver) wereprocessed for histological studied (formalin fixed, alcohol series, 6 sliced and HE Stained).Result indicate that the structure of liver of the treated fish showing abnormality symptoms,such as necrosis, fatted degeneration and hemorrhage. It can be concluded that feeding offish with 30 g of Psidium guajava and 30 g of Andrographis paniculata Ness is able to treatA. hydrophila infection on Mystus nemurus.Key word : Liver, Mystus nemurus, Psidium guajava, Andrographis paniculata Ness.